(untitled) (BIS Humanities and Social Science, 2026)
This study investigates how the Communication and Information Agency (Diskominfo) in Kuningan Regency handles their Instagram account @kominfokuningan to share public service information in 2024. Instagram has become an important way for local governments to share information, talk back and forth with people, and get more involvement from the public in their programs and policies. This study uses a qualitative descriptive approach, gathering data through interviews and written records. The results show that the @kominfokuninan account is working well, using feeds, reels, stories, and live features to share public service education and information in a creative, interactive, and consistent way. This success is because of a focused content plan, regular check-ins, and adjusting to new online trends. This study found that having not enough people and money is making it hard to manage the @kominfokuningan account. To overcome these limitations, the @kominfokuningan account uses more people, including interns, and also uses personal tools from the management team to create content. The study’s results indicate that managing the @kominfokuningan Instagram account has worked well as a way to share public service information. It supports the idea of good digital governance by focusing on transparency, accountability, and involving the community. The use of social media helps build a better image for the local government and makes people in Kuningan Regency more skilled in using digital tools.